2009
DOI: 10.1016/j.antiviral.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inhibition of porcine reproductive and respiratory syndrome virus replication by combination of morpholino oligomers

Abstract: Porcine reproductive and respiratory syndrome (PRRS) has caused heavy economic losses in the swine industry worldwide and current strategies to control PRRS are inadequate. Previous studies have shown that peptide-conjugated phosphorodiamidate morpholino oligomer (PPMO) can be an effective antiviral against the PRRS virus (PRRSV). PPMO is structurally similar to DNA with modified backbone and is resistant to nuclease. This study was designed to examine increasing inhibitory effect of PPMO combination. Two pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For the quantification of purified virus, PRRSV RNA was analyzed using quantitative real-time RT-PCR with primers designed against PRRSV ORF7 (Patel et al, 2008). A plasmid containing ORF7 sequence was used to generate a standard curve, and RNA copies in all samples were calculated based on it (Han et al, 2009). The transcript levels of cell-associated viral RNA were relatively quantified by the 2-ΔΔCT Method (Livak and Schmittgen, 2001).…”
Section: Quantitation Of Viral Rnamentioning
confidence: 99%
“…For the quantification of purified virus, PRRSV RNA was analyzed using quantitative real-time RT-PCR with primers designed against PRRSV ORF7 (Patel et al, 2008). A plasmid containing ORF7 sequence was used to generate a standard curve, and RNA copies in all samples were calculated based on it (Han et al, 2009). The transcript levels of cell-associated viral RNA were relatively quantified by the 2-ΔΔCT Method (Livak and Schmittgen, 2001).…”
Section: Quantitation Of Viral Rnamentioning
confidence: 99%
“…Therefore, successful supplementary strategies should include antiviral drugs and immune-modulation therapies (Benfield et al, 2002;Du et al, 2011;Han et al, 2009;Jiang et al, 2010;Karuppannan et al, 2012;Keirstead et al, 2008;Kreutz & Ackermann, 1996;Li et al, 2009;Opriessnig et al, 2011;Patel et al, 2008;te Velthuis et al, 2010;van der Meer et al, 2007;Wei et al, 2011;Yang et al, 2013;Zhuge et al, 2012). When evaluating the antiviral effect of tilmicosin against PRRSV, our data suggested that tilmicosin would be effective in reducing the PRRSV loads in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that reducing the PRRSV load in the serum may prevent pigs from developing clinical signs after PRRSV infection. Several studies have attempted to identify effective anti-PRRSV treatments in vitro and in vivo (Benfield, Chase, Moore, Wagner, & Zeman, 2002;Du, Yoo, Paradis, & Scherba, 2011;Han, Fan, Patel, & Zhang, 2009;Jiang, Fang, Luo, Xiao, & Chen, 2010;Karuppannan, Wu, Qiang, Chu, & Kwang, 2012;Keirstead, Lee, Yoo, Brooks, & Hayes, 2008;Kreutz & Ackermann, 1996;Li et al, 2009;Opriessnig et al, 2011;Patel et al, 2008;te Velthuis et al, 2010;van der Meer et al, 2007;Wei et al, 2011;Yang et al, 2013;Zhuge et al, 2012). However, there are no effective commercial drugs available to prevent PRRSV infection in pigs in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses and arteriviruses are RNA viruses that share similar genomic structures. PMOs and arginine-rich peptide-conjugated PPMOs directed against the 5 0 UTR of equine arteritis virus (EAV) and against the 3 0 UTR of porcine reproductive and respiratory syndrome virus (PRRSV), respectively, have exhibited antiviral activity in in vitro translation assays and in cell culture (Han et al, 2009;Patel et al, 2008;van den Born et al, 2005;Zhang et al, 2006). Regions of the arterivirus genome which can be inhibited by PMOs have also shown to be target regions for inhibiting CoV.…”
Section: Use Of Morpholino Asos During Viral Infectionsmentioning
confidence: 99%